2021
DOI: 10.21203/rs.3.rs-249723/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mean Arterial Pressure Should Above 65 mmHg at Vasopressor Weaning — Exploratory Study of Optimal Weaning Blood Pressure for Patients in Intensive Care Unit

Abstract: Objective:Vasopressors are one of the main treatments for severe hypotension or shock, which commonly occurs in intensive care unit (ICU) patients. However, only a few studies have been conducted on the appropriate timing for vasopressor weaning. This study aims to explore the effect of blood pressure at vasopressor weaning on the probability of in-hospital mortality.Design: Single-center retrospective observational study.Setting: ICU from Beth Israel Deaconess Medical Center between 2008 and 2019.Patients: IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been suggested that inotropic usage should be started early in septic shock cases to maintain a MAP of at least 65 mmHg and organ perfusion while waiting for the antibiotic to produce a response and the infection source to be controlled ( 11 ). The ideal course of treatment based on prior literature is to reduce inotropes as the targeted MAP is achieved ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that inotropic usage should be started early in septic shock cases to maintain a MAP of at least 65 mmHg and organ perfusion while waiting for the antibiotic to produce a response and the infection source to be controlled ( 11 ). The ideal course of treatment based on prior literature is to reduce inotropes as the targeted MAP is achieved ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%